The influence of pricing and advertising on customer pleasure as mediated by purchase decisions - Ferry Cahaya, Yohanes; Putri Nofzil, Friska; Yosepha, Sri Yanthy; Pujiati, Herni; Setyanto, Eddy (Management Research Studies Journal, 2024)
This study aims to examine the influence of price and advertising on consumer satisfaction through purchase decisions. This study employs a quantitative methodology. This study utilized a sample of 100 participants from the Shopee program. The questionnaire results provided the research data, which was analyzed using the SEM PLS method through the SmartPLS 3.0 application. The results of this study indicate that: (1) Price has a positive and substantial impact on purchase decisions. Advertising elements significantly and positively impact purchasing decisions. Acquisition decisions significantly and positively impact client satisfaction. The coefficient of determination for consumer satisfaction is 0.681. Price, advertising, and purchasing decisions constitute 68.1% of the variance in consumer satisfaction among users of the Shopee program, while other factors account for the remaining 31.9%.